Academic Burnout in University Students During Covid-19 Pandemic: Viewed from Readiness to Change with Religious Coping as a Moderator - Aryo Bima Fathoni; Nisrina Zulfa; Ila Nurlaila Hidayat (Universitas Islam Tribakti Lirboyo Kediri, 2022)
The COVID-19 pandemic has resulted in various problems in almost all aspects of life, one of which is education. As one of the educational institutions, universities have finally implemented distance learning to reduce the spread of the virus on campus. However, this policy can also cause several new problems for students, including unpreparedness and boredom when implementing distance learning. This study aimed to determine the effect of readiness to change on university students’ academic burnout and to prove that religious coping as an internal resource can strengthen its influence. This research used quantitative research, especially correlational research design, using a hierarchical regression test to compare the results of the effect with and without the moderating variable. The sampling technique used in this study was a non-probability sampling with an accidental sampling technique in which it was obtained 300 active university students from the provinces of DKI Jakarta, West Java, and Yogyakarta. The results of the analysis showed that readiness to change could explain the academic burnout variance by 27%. Religious coping can be a moderator and strengthen the effect of readiness to change on academic burnout with a beta coefficient of -.003, which means an increase in one readiness to change score and religious coping can reduce academic burnout by 3%.